2022
DOI: 10.1021/acsmaterialslett.2c00013
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of a Water-Soluble Catechol-Functionalized Binder for Silicon Anodes by Diverse In Situ Analyses

Abstract: Traditional binders generally interact with silicon particles via weak van der Waals forces and consequently lack interactions between active materials after volume expansion. Water-soluble binders have recently garnered lots of attention as low-cost and environmentally benign aqueous media to overcome the main challenges with practical processing considerations. Herein, we report the development of a multifunctional polymeric binder having a three-dimensional network structure for silicon-based anodes, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Ko et al developed a new 3D binder DPA with three units: poly­(ethylene-glycol)-diacrylate (PEGDA), dopamine methacrylamide (DMA), and poly­(ethylene glycol) monomethyl ether-acrylate (PEG). Among the three units, PEGDA acts as cross-linker between the backbones of the linear polymer to form a 3D network structure, and by in situ observations at the nanoscale and microscale levels, the 3D binder can mitigate the microstructural changes and maintain structural integrity against expansion to improve the cycle life of the LIBs . The in situ preparation of 3D binder can overcome the processing difficulties and effectively simplify the process of the electrode fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ko et al developed a new 3D binder DPA with three units: poly­(ethylene-glycol)-diacrylate (PEGDA), dopamine methacrylamide (DMA), and poly­(ethylene glycol) monomethyl ether-acrylate (PEG). Among the three units, PEGDA acts as cross-linker between the backbones of the linear polymer to form a 3D network structure, and by in situ observations at the nanoscale and microscale levels, the 3D binder can mitigate the microstructural changes and maintain structural integrity against expansion to improve the cycle life of the LIBs . The in situ preparation of 3D binder can overcome the processing difficulties and effectively simplify the process of the electrode fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three units, PEGDA acts as cross-linker between the backbones of the linear polymer to form a 3D network structure, and by in situ observations at the nanoscale and microscale levels, the 3D binder can mitigate the microstructural changes and maintain structural integrity against expansion to improve the cycle life of the LIBs. 38 The in situ preparation of 3D binder can overcome the processing difficulties and effectively simplify the process of the electrode fabrication. Guo et al synthesized the γ-PGA-PAA polymer binder though an in situ thermally crosslinking method to form a 3D network structure, which is sufficient to keep the structure integrity of the electrode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the increasing development of electric vehicles, portable devices, and energy storage systems, considerable attention is being paid to improving the energy density of lithium-ion batteries (LIBs). Although graphite-based materials are the most commonly used materials for anodes in commercial LIBs, the improvement in energy density is limited due to their relatively low theoretical capacities (e.g., capacity = 372 mA h g –1 based on LiC 6 ) . Silicon has been considered as a promising anode material due to its high theoretical capacity (4200 mA h g –1 ), low discharge potential (∼0.3 V vs Li/Li + ), and natural abundance. However, since Si undergoes a significant volume change of up to 300% during charging/discharging, the electrode structure is degraded, and a thick solid–electrolyte interface (SEI) layer is formed, which is the critical disadvantage in practical application of the Si anodes. , One of the main strategies to mitigate the Si volume change is to adopt nanostructured Si as the anode material, such as yolk–shell nanoparticles, , nanowires, , and nanoporous structures. , Although nanostructured Si anodes have been known to reduce Si volume expansion to some extent, the commercialization of these materials is hampered by high production costs and difficulty in scaling-up the manufacturing process …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we performed operando optical microscopy analysis to investigate temporal and spatial variations in the Li concentration within the electrodes in terms of kinetics, as the information inferred by d Q d V –1 plots correspond to an average value of the active materials in the electrode. , When we examined the reaction dynamics of graphite and the composite electrodes at 0.2C, we found that both active materials turned yellow from the electrode surface toward the interior, indicating that lithiation reactions occur from the electrode/electrolyte interface toward the bulk (Figure S8 and Videos S1, S2); the yellow particles refer to fully lithiated graphite (LiC 6 ). In addition, these results confirmed that this depth heterogeneity of lithiation on graphite is much more pronounced at 1.0C, causing unwanted Li plating, as shown in Figure b and Video S3, which is closely related to the sluggish mass transport through electrolytes and bulk diffusion in a porous electrode. , In the early stage of fast charging, graphite particles react normally near the electrode surface; however, the reaction front no longer propagates into the bulk.…”
mentioning
confidence: 99%